The Influence of Service Quality and Price on Loyalty of Users of Way Jepara East Lampung Online Motorbike Taxi Services (Case Study of Go-Star and Cetar Way Jepara East Lampung Customers) - Hikmatul Aliyah; Septiana Mar'atus Sholikhah; Yolla Zelika D; Adi Prayoga (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the relationship between service quality and price on online  motorcycle taxi user loyalty way jepara, especially Go-Star and cetar users. This research  method uses quantitative research, which is a method to test certain theories by using how to  examine the relationship between variables, then measuring with research instruments by  distributing questionnaires to Go-Star and cetar online motorcycle taxi users. The questionnaire  measures key variables such as service quality, price and user loyalty. The data collected is then  analyzed using appropriate statistical techniques. The results of research that has been conducted by researchers can be concluded that the  service quality variable (X1) is partially tested on the loyalty of online motorcycle taxi users  resulting in a t test significant value of 0.000 smaller than 0.05 (0.000 0.05). The price variable  (X2) partially tested on the loyalty of online motorcycle taxi users resulted in a t test significant  value of 0.004 smaller than 0.05 (0.004 0.05). service quality and price variables are tested  simultaneously on the loyalty of online motorcycle taxi service users the calculated F value is  greater than the F table value, namely F count 80.423 3.09 and also a value and also a  significant value of 0.000 0.05